A survey of the weevils of Ukraine (Coleoptera: Curculionoidea) - Yunakov, Nikolai; Nazarenko, Vitalij; Filimonov, Rostislav; Volovnik, Semyon (Zootaxa, 2018)
The fauna of weevils Curculionoidea of Ukraine numbers 1453 species equivalent to 25.3% of European fauna. They belong to 10 families and 364 genera. A total of 51 species are recorded from Ukraine for the first time. Assessment of inventory completeness indicates that 62% of the area of Ukraine are covered by samples. Spatial join analysis has reveals strong collecting biases and shows maximal richness in cells which fall into well-sampled provinces. A total of 22 out of 33 studied model sites are well-sampled (C>0.5). In total, we estimate ca.1470 species of Curculionoidea living in Ukraine. Curculionidae comprise the majority (82%) of the fauna, with 1202 species and 266 genera, and with remarkably high proportion of the three largest subfamilies: Entiminae (26%), Curculioninae (19%), and Ceutorhynchinae (18%). Consolidated data analysis shows highest richness (678–822 spp.) in provinces which fall into the mountain areas. Aggregated species richness for each of five ecoregions uncovers highest values in Pontic steppe (665 species) and East European forest-steppe (593 species). Habitat distribution of weevils is strongly uneven. Most of the richness (565 spp.) is harboured in lowland broadleaf forests. Salt marshes, salt steppes and sands are extreme habitats with low richness but high proportion of habitat specialists. Only 141 dominant species representing 18% of the total fauna but make up to 63% of the total population of weevils in Ukraine. Endemic species comprise a small proportion of the fauna but are remarkably concentrated in the mountains of Crimea (24 species) and the Carpathians (25 species). Along with ‘true’ endemics, 210 species are narrowly-ranged non-endemics and also have higher concentration in Crimea and the Carpathians (105 and 38 spp.). A total of 82 species are qualified as widely-ranged with high concentration in Central European Mixed Forests and East European Forest Steppe (71 spp. on average per province). The high diversity and evenness of weevil assemblages is shown by species sequence curve analysis in the Crimean Mountains, the Carpathians, steppes and lowland broad leaf forests, which contrasts with assemblages in lowland mixed forests. Shannon-Wiener and Simpson indices both show an extremely broad range of evenness in the Pontic Steppes which have both assemblages with low evenness in Stipa-Festuca-Koeleria steppes and high evenness in Stipa-Bromopsis steppes (H’ =1.87–4.22). East European Forest Steppe and Central European Mixed Forests harbour similarly even communities (H’ =3.60–4.48 vs. 3.18–4.57). The Crimean Mountains and the Carpathians are defined as a hotspot of biodiversity combining the highest scores of endemics, R1 species, and highest alpha diversity. Host plants are documented for 1259 species. Some 83% of weevils feed on live tissues of angiosperm plants belonging to 64 families. A total of 258 species are confirmed as polyphagous, 8 as monophagous, thus the majority of the rest are more or less narrowly oligophagous. A total of 33.68% of the species are associated with Fabaceae, Asteraceae, and Brassicaceae.